2008
DOI: 10.1063/1.2828045
|View full text |Cite
|
Sign up to set email alerts
|

Quantized electronic properties of diamond

Abstract: A review of electronic properties of insulating-, boron-and phosphorus-doped diamond is given. The main goal is, to show data in a wider context, to reveal trends and limitations with respect to carrier mobilities, conductivities, p-and n-type doping. Undoped diamond is an insulator with conductivities significantly smaller than 10 -17 Ωcm at room temperature.Mostly, these insulating films show conductivity activation energies of 1.7 eV, an indication that small amounts of substitutional nitrogen dominates the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 67 publications
0
5
0
Order By: Relevance
“…For scientific and technological applications, its high chemical and mechanical resilience, high surface stability, high thermal conductivity, and wide bandgap make diamond a promising candidate in the fields of electrochemistry, heat spreaders, biological platform, sensor devices, protective coatings, and so forth , . Several of these applications require very thin diamond layers (<100 nm) with a low surface roughness, for bioinert layers in biocell interfacing , for example, as well as for high-reactivity electrochemical applications or electronics , thus increasing interest in an improved control of diamond nanocrystalline film growth.…”
Section: Introductionmentioning
confidence: 99%
“…For scientific and technological applications, its high chemical and mechanical resilience, high surface stability, high thermal conductivity, and wide bandgap make diamond a promising candidate in the fields of electrochemistry, heat spreaders, biological platform, sensor devices, protective coatings, and so forth , . Several of these applications require very thin diamond layers (<100 nm) with a low surface roughness, for bioinert layers in biocell interfacing , for example, as well as for high-reactivity electrochemical applications or electronics , thus increasing interest in an improved control of diamond nanocrystalline film growth.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming that the energy difference between the vacuum level and the surface Fermi level ͑FL sur ͒ dominates field emission from the SCL on H-terminated intrinsic diamond, the effective emission barrier height of region ͑iii͒ is 5.3 eV. 11 From these data, we conclude that the 2D levels act as electron source for emission. 3 eV, the Fermi level would then be 0.8-1.2 eV below the valence band, maximum at the surface of diamond.…”
Section: ͑2͒mentioning
confidence: 75%
“…Although the transfer-doping model seems to be the most appropriate mechanism for the generation of this effect, the electronic properties of the surface conductive layer ͑SCL͒ have hardly been discussed up to now. 11 Defined electrolyte solution, as well as adsorbate layers formed from the atmosphere, were used to establish transfer doping and to generate surface conductivity on diamond surfaces. Numerical solutions of the Poisson and Schrödinger equations 10 showed that a two-dimensional ͑2D͒ electronic structure was formed at the surface of diamond.…”
Section: Resonant Field Emission From Two-dimensional Density Of Statmentioning
confidence: 99%
“…Much interest was generated by the synthesis of this easily processable polymer and the report of its conversion to diamond and DLC by means of pyrolysis [1]. Diamond has been reported to have interesting electrical properties [2,3] and applications in MEMS [4] and biology [5]. And ta-C:H has also been shown to be relevant to the electrical and biological communities in the form of protectivecoatings in magnetic disk memories [6] and a haemocompatible material [7], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Poly(hydridocarbyne) (PHC) is an sp 3 hybridized random network carbon polymer, comprised of amonomeric unit containing one carbon-hydrogen and three carbon-carbon single bonds not unlike hydrogenated tetrahedral amorphous carbon (ta-C:H). Much interest was generated by the synthesis of this easily processable polymer and the report of its conversion to diamond and DLC by means of pyrolysis [1].…”
Section: Introductionmentioning
confidence: 99%